DAGESTAN IN THE IRAN-TURKEY CONFRONTATION IN THE CAUCASUS AT THE END OF THE XVI - THE BEGINNING OF THE XVII CENTURY - Murtazaev, A O; Allaev, N M (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers the role and place of Dagestan in the confrontation between the Ottoman Empire and Safavid Iran for hegemony over the Caucasus that took place in the late 16th–early 17th centuries.
Keywords: Dagestan; confrontation; uprising; Safavid Iran; Ottoman Empire; invasion; troops